Advances in the Use of the Steel Industry by-products when Manufacturing Traditional Ceramics for Sustainable Purposes. (2015) - Mendoza-Cuenca, J.L.; Mayorga, M.; Romero-Salazar, L.; Yee-Madeira, H.T.; Jiménez-Gallegos, J.; Arteaga-Arcos, J.C.
Abstract: The ceramic industry is not only one of the most profitable worldwide industries, but also a large carbon footprint one, mainly due to the use of virgin raw non-renewable materials and high consumption of fuels. On the other hand, the steel industry produces by-products as blast furnace and electric arc furnace slag that can be recycled in other manufactures. These slags are mainly composed of alumina, silica, calcium oxide, magnesium oxide and iron oxide, which are some of the components of ceramic raw materials. Blast furnace slag is widely used in the cement industry as a clinker replacement for the manufacturing of the Composite Portland Cement, a less carbon footprint product when compared besides Ordinary Portland Cement. In this research, we communicate some preliminary laboratory-scale results when including steel slags in traditional processes of ceramic manufacturing. We completely replaced kaolin by slag and designed different ceramic compound mix formulations. We report some fresh and sintered properties such as dry shrinkage and porosity. This investigation is part of a major project focused on the development of a methodology for the utilization of steel by-products in the industrial-level manufacturing of traditional ceramic products especially tiles and building bricks.